Analisis Perbandingan Antara Rasio Keuangan dan Metode Economic Value Added (EVA) Sebagai Alat Ukur Kinerja Keuangan Perusahaan Pada PT. Japfa Comfeed Indonesia tbk - Novi Irmalasari (KITABAH: Jurnal Akuntansi dan Keuangan Syariah, 2021)
This study aims to analyze the comparison between financial ratios and the method of economic value added (EVA) as a means of measuring the company's financial performance at PT. Japfa Comfeed Indonesia Tbk. This study uses a qualitative descriptive approach, aims to determine the comparison between financial ratios and the method of economic value added (EVA) as a means of measuring the company's financial performance at PT. Japfa Comfeed Indonesia Tbk. The subject of this research is PT. Japfa Comfeed Indonesia Tbk and the object of this research is the income statement and balance sheet of PT. Japfa Comfeed Indonesia Tbk in 2018-2020. The analysis technique used is qualitative. From the results of the analysis that has been done, it can be concluded that based on the value of the financial ratios generated by PT. Japfa Comfeed Indonesia Tbk is positive. That is, the company is still able to earn a profit from the management of its total assets, so it can be said that the company's financial performance is classified as good. From the analysis that the author has done, it can be concluded that based on the Economic Value Added (EVA) method, it is known that the financial performance of PT. Japfa Comfeed Indonesia Tbk is classified as good. this is evidenced by the existence of a positive EVA value which indicates that the rate of return generated by the company exceeds the rate of return demanded by investors. This means that the company is able to obtain added economic value for its business.